Owner-occupied housing costs, policy communication, and inflation expectations - Joris Wauters; Zivile Zekaite; Garo Garabedian (National Bank of Belgium, 2024)
The ECB concluded its strategy review in 2021 with a plan to include owner-occupied housing (OOH) costs in its inflation measure in the future. This paper uses the Bundesbank's online household panel to study how household expectations would react to this change. We conducted a survey experiment with different information treatments and compared long-run expectations for euro area overall inflation, interest rates, and OOH inflation. Long-run expectations are typically higher for OOH inflation than overall inflation, and both are unanchored from the ECB's target at the time of the survey. We find significantly higher inflation expectations under the treatment where OOH costs are assumed to be fully included in the inflation measure. This information effect is heterogeneous as, among others, homeowners and respondents with low trust in the ECB react more strongly. However, inflation expectations remain stable when information about past OOH inflation is also given. Careful communication design could thus prevent expectations from becoming more de-anchored.
Keywords: D83; D84; E31; E50; 330; Owner-occupied housing costs; survey experiment; inflation measurement; inflation expectations; ECB